(3WQGR GdeMGad aj Md CdZGR GdeSGFds - (3YHO GdQMje Hf GdMSf Hf Ydj GdESfhj GdTGaYj, CHh eMeO, LeGd GdOjf,J (B772 (3g` s ((3YHO GdQMef Hf YHO Gddg Hf Nda GdJQeSi GdKZQi GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg GdYdje HeG JdZRg GdCdaGX GdNHjQ HeG JQeRg GdCdMGX GdMajX HeG JYLR Yf MaXg GdMaGX s
(3BNQgG (B:s
(3Je GdcJGH GdeHGQc hGdMeO ddg hMOgq s
(3HgG fXGe GdJYbjHIs
(3Ydi dhMI GdYfhGf JedcGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B344 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B203s
Keywords: (3Gdabg GdTGaYjs